Gérard Chazal: Bachelard topics in the work of François Dagognet - Ples-Bęben, Marta (Folia Philosophica, 2021)
Polish translation of an article by Gérard Chazal, devoted to the relationship of François Dagognet’s philosophy to the work of Gaston Bachelard. The author shows the complexity of this relationship, analyzing it in relation to the philosophy of science (here, among others, analyzes the issue of the historicity of the process of formation of the knowledge), the philosophy of technology and the philosophy of art. In many dimensions Chazal shows that Dagognet was inspired not so much by the letter of Bachelard’s texts as by their spirit, using his methods and concepts in areas that Bachelard was not or only marginally interested in (including in the biological and medical sciences, in the visual arts). The article is also an interesting voice in the discussion about the essence of the reception of philosophical concepts and currents. In this aspect author asks about the negation of the source theory in its continuations at the same time asking whether it is not this kind of negative inspiration that best testifies to the vitality of the theory — alive due to constant creative transformations.